2021
DOI: 10.12688/f1000research.27189.3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological burden of the COVID-19 pandemic and its associated factors among frontline doctors of Bangladesh: a cross-sectional study

Abstract: Background: Frontline doctors are the most vulnerable and high-risk population to get the novel coronavirus disease 2019 (COVID-19) infection. Hence, we aimed to evaluate the anxiety, depression, sleep disturbance and fear of COVID-19 among frontline doctors of Bangladesh during the pandemic, and the associated factors for these psychological symptoms. Methods: In total, 370 frontline doctors who were involved in the treatment of suspected or confirmed COVID-19 patients during the pandemic took part in an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 28 publications
2
52
1
7
Order By: Relevance
“…Prevalence of mental disorders: Healthcare professionals Due to close contact with the COVID-19 infected and/or suspected patients, the healthcare professionals generally experience higher psychological distresses. Only four studies were conducted focusing on the mental health of the healthcare professionals, whereas the prevalence of depression and anxiety ranged from 34.2-48.5% and 32.5-69.5%, respectively (22,24,25,40). Nevertheless, stress was not reported in any of the studies.…”
Section: B Prevalence Of Mental Disorders: Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prevalence of mental disorders: Healthcare professionals Due to close contact with the COVID-19 infected and/or suspected patients, the healthcare professionals generally experience higher psychological distresses. Only four studies were conducted focusing on the mental health of the healthcare professionals, whereas the prevalence of depression and anxiety ranged from 34.2-48.5% and 32.5-69.5%, respectively (22,24,25,40). Nevertheless, stress was not reported in any of the studies.…”
Section: B Prevalence Of Mental Disorders: Studentsmentioning
confidence: 99%
“…Gender was found to be a signi cant predictor of mental disorders in a large number of studies (8, 14,[19][20][21][22][24][25][26]29,30,32,35,36,[38][39][40]. A study found that females were suffering mostly from depression, anxiety, and stress, respectively, where it was 3.4-, 3.4-and 4.5 times higher than males (19).…”
Section: B Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 presents the collected data with corresponding interpretation towards analysed sleep quality in healthcare givers. The analysed data indicate that working with COVID-19-affected patients is associated not only with a poorer sleep quality and insomnia symptoms, but also with mental health risks such as increased stress and burnout as well as a strong predisposition to mental disorders such as depression and anxiety [56,57,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Sleep Quality In the Healthcare Givers Under The Covid-19 Pandemic Conditionmentioning
confidence: 99%